2021
DOI: 10.1021/acs.orglett.1c02792
|View full text |Cite
|
Sign up to set email alerts
|

[3 + 2] Coupling of Quinone Monoacetals with Vinyl Ethers Effected by Tetrabutylammonium Triflate: Regiocontrolled Synthesis of 2-Oxygenated Dihydrobenzofurans

Abstract: The synthesis of 2-oxygenated dihydrobenzofurans involving the [3 + 2] coupling of quinone monoacetals with vinyl ethers has been realized by tetrabutylammonium triflate catalysis. The reaction involves a new activation method of the acetal moiety in quinone monoacetals under acid-free conditions affording the highly oxygenated dihydrobenzofurans. This new activation mode was achieved by using the triflate anion catalyst for stabilization of the highly reactive cationic intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Yasuyuki Kita et al revealed in 2021 an efficient and novel strategy for constructing 2-oxygenated 2,3-DHB derivatives 116 via n Bu 4 NOTf catalyzed [2 + 3] coupling of vinyl ethers 115 and quinone monoacetals 114. [112] The 2-oxygenated 2,3-dihydrobenzofurans 116 are formed through a novel activation technique of the acetal moiety in quinone monoacetals 114 in acid-free circumstances. The triflate anion (TfO À ) catalyst stabilized the exceedingly volatile cationic intermediate, resulting in this unique activation mode.…”
Section: The Construction Of 2-oxygenated Dhbs From Quinone Monoacetalsmentioning
confidence: 99%
“…Yasuyuki Kita et al revealed in 2021 an efficient and novel strategy for constructing 2-oxygenated 2,3-DHB derivatives 116 via n Bu 4 NOTf catalyzed [2 + 3] coupling of vinyl ethers 115 and quinone monoacetals 114. [112] The 2-oxygenated 2,3-dihydrobenzofurans 116 are formed through a novel activation technique of the acetal moiety in quinone monoacetals 114 in acid-free circumstances. The triflate anion (TfO À ) catalyst stabilized the exceedingly volatile cationic intermediate, resulting in this unique activation mode.…”
Section: The Construction Of 2-oxygenated Dhbs From Quinone Monoacetalsmentioning
confidence: 99%